Literature review: Menginduksikan Nilai-Nilai Budaya Minang dalam Proses Konseling - Affan Yusra; Kheylyla Adha Pierda; Ermida Lestari; Harti Zakia Nopitri; Nurnilamsari Nurnilamsari; Sinta Nurzulina Putri (Journal on Education, 2023)
Among the many ethnic groups in Indonesia, the largest ethnic group in Indonesia, one of which is the Minangkabau. As we understand, Indonesia is a country that has a diversity of values ​​and culture in everyday life. The activities of human life are certainly inseparable from the obstacles or obstacles that occur, therefore counseling services are present in the midst of life to provide assistance, both individually and in groups, so that obstacles that occur are resolved by mutual agreement between the counselor and the client. Minangkabau cultural values ​​have harmony in the process of counseling services, such as the value of deliberation, the value of giving awards to others, and the value of conscientiousness. With this alignment, it is hoped that the process of providing counseling services can run according to procedures without any obstacles. The interaction between the counselor and the counselee becomes interactive as a result of the harmony between Minang cultural values ​​and the counseling service process.